RELEVANSI NILAI KEBAJIKAN DALAM KEBIJAKAN KOMUNIKASI: MEMAKNAI INFORMASI FUNDAMENTAL DARI PERSPEKTIF INVESTOR - Made Sudarma; Putu Prima Wulandari (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2022)
The purpose of this research is to reveal the meaning of fundamental information from the perspective of investor in their process of making investment decision. Qualitative approach is used in extracting the meaning of investor’s understanding and experience in natural perspective. Interpretive paradigm is used to lead the researchers’ way of thinking in studying human and their experiences. Transcendental phenomenology is used to reveal the awareness phenomenon in experience understood by the informants. Informant’s awareness is a simple format yet can be used to gain deep understanding. The research finding shows that fundamental information is interpreted as macro and micro information which is connected to each other. The second finding describes the interpretation of fundamental information for investor as a communication policy that should be based on virtue value to induce investor’s trust, comfort and confidence level in making decision. Virtue value in this case is the accountability with company’s good intention in revealing fundamental information, both in form of positive predictive value and negative predictive value. The investor’s dependency of fundamental information in form of financial reports invokes investor’s awareness that virtue value in company’s communication policy is the main value relevance.